THE DESIGN OF A PUSH-PULL SWITCH MODE POWFR SUPPLY FOR AC DRIVES - Dalci, K. Burak; Gulez, Kayhan; Cansever, Galip (IEEE, 2004)
In this study, the step up DC-DC converter that works in push-pull connection has been taken up. The voltage-drops that occured since input voltage was low, have been minimized. The IRF 1310N mosfet which had minimum conduction resistance was preferred when we were selecting semiconductor elements used for voltage-drop minimization. As the current value switched in converter was high, the current capacity was increased by connecting the mosfets as parallel. At the same time the voltage-drop occured on semiconductor element, was minimized. Switching mode power supply at 28 kHz is capable of providing 380 Watt. It gives the input power from B standard 12 volt battery, and its output voltage is 311V. As the realized converter has the closed loop feature, output voltage remains stable within determined power limits. When the converter is used as pre-circuit of the inverter, it simplifies the control cards highly as the inverter input voltage remains constant. Converter design shows that theoretical analyses and experimental results are in accordance with.
Keywords: Engineering